Evaluation of Serum Magnesium, Iron, Copper and Zinc Levels in Ischemic and Hemorrhagic Stroke Patients and Healthy Controls - Hojatollah Moemeni; Durdi Qujeq; Alijan Ahmadi Ahangar; Karimollah Hajian; Hadi Parsian (Golestan University Of Medical Sciences, 2018)
Introduction: Many studies have shown a relationship between serum level of trace elements and risk of stroke, but the exact mechanism of this relationship is not clear. The purpose of this study was to measure changes of serum magnesium, iron, copper, and zinc levels in ischemic and hemorrhagic stroke patients to evaluate their potential diagnostic utility.Materials and methods: Overall, 53 healthy individuals (30 men, 32 women) and 53 ischemic and hemorrhagic stroke patients (30 men, 23 women) who were admitted to the Rouhani Hospital in Babol (Iran) were enrolled in the study within 24 hours after stroke onset. Diagnosis was made based on medical history and physical examination by a neurologist. After blood sampling, serum copper was assessed by atomic absorption spectrophotometry, and zinc, magnesium and iron levels were assessed by spectrophotometry. Data analysis was performed in SPSS (version 21) using independent sample t-test and chi-square test. Results: Serum concentrations of copper was significantly higher in the patients (58.8 ±14.7 mg/dL) compared with the controls (45.7 ±10.0 mg/dL). Serum concentrations of zinc was significantly higher in the patients (113.2 ±17.3 mg/dL) compared with the controls (95.60 ±12.80 mg/dl). Moreover, serum concentrations of iron was significantly higher in the patients (148.5 ±30.4 mg/dL) compared with the controls (74.22 ±33.3 mg/dL). However, the patients (1.4 ±0.8 mEq/L) had significantly lower level of magnesium level compared to the controls (2.1 ±0.3 mEq/L). Conclusions: Our results suggest that evaluation of serum magnesium, iron, copper and zinc levels in ischemic and hemorrhagic stroke patients may be useful for the prediction and diagnosis of stroke status.